Exploring the world. Victoria Falls (Academic Video Online, 2013)
The Scottish explorer Dr. David Livingstone was the first white person to discover Victoria Falls and named them in honor of Queen Victoria. Also known locally as Mosi-oa-Tunya, which means "the Smoke that Thunders," the falls have been named "One of the Seven Natural Wonders of the World," and this program, with its spectacular aerial footage that offers a bird's-eye view of the falls and the Zambezi River (literally, the "Great River"), proves why. The falls' width and height form the largest sheet of falling water in the world; also their unusual form allows visitors to view the whole width of the falls face-on. It is no wonder that the falls are one of Africa's major tourist attractions, as well as a UNESCO World Heritage Site. Shared between Zambia and Zimbabwe, each country has a national park to protect the falls and a town that serves as a tourism center. On the Zimbabwe side, we visit the Victoria Falls Hotel, a featured landmark, built in 1904, to accommodate travelers as a result of Cecil Rhodes' dream to bring the railway from Cape Town to Cairo. Also, in the Falls Crafts Village, we learn that bargaining is a way of life in this shopping center known for its woodcarvings and sculptures.